Analysis of vaccine coverage against influenza in the region of Cocais - Piauí - from 2011 to 2013 - Paula Lima da Silva; Francisca Miriane de Araujo Batista (Universidade de Santa Cruz do Sul, 2015)
Background and Objectives: The detailed study of vaccination coverage is able to demonstrate aspects of health care and the performance of services, to provide subsidies for the process of planning, as well as help in the restructuring of actions. The main objective of this study is to analyze the vaccination campaign coverage against influenza in the region of Cocais, from 2011 to 2013. Methods: This is an epidemiological descriptive study with a quantitative approach. It was carried out in the region of Cocais, state of Piaui, Brazil, with data related to the period of 2011 to 2013, collected from the Ministry of Health Information System (in Portuguese, DATASUS). Results: Based on the analyzed data of the assessed triennium, it became possible to identify that some towns did not manage to reach the minimum target established by the Ministry of Health, which corresponds to 80% of vaccination coverage for each priority group. As for the groups, they did not show homogeneity in some towns and periods. It is important to highlight that the group of pregnant women showed the lowest percentage, mainly in 2011. It was observed that, except for the group of pregnant and puerperal women, there are differences between the groups regarding the reasons for noncompliance with the vaccination schedule. Conclusion: The individual evaluation of the vaccination campaign is crucial to understand the local circumstances of each town and to plan the differentiated actions, taking into account the necessities of each town and, particularly, of each group.